2021
DOI: 10.1140/epjc/s10052-021-09537-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the hyperscaling violation and dynamical exponents on the imaginary potential and entropic force of heavy quarkonium via holography

Abstract: The imaginary potential and entropic force are two important different mechanisms to characterize the dissociation of heavy quarkonia. In this paper, we calculate these two quantities in strongly coupled theories with anisotropic Lifshitz scaling and hyperscaling violation exponent using holographic methods. We study how the results are affected by the hyperscaling violation parameter $$ \theta $$ θ and the dynamical exponent z at finite temperature and chemical potential. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…It was found that the entropy increases with the inter-quark distance, and the peak of the entropy emerges when the U-shaped string stretched between the touches the horizon of the black hole. Subsequently, there have many attempts to address the entropic force in this direction [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the entropy increases with the inter-quark distance, and the peak of the entropy emerges when the U-shaped string stretched between the touches the horizon of the black hole. Subsequently, there have many attempts to address the entropic force in this direction [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, people used this method several times, for example, for a static [13,14] and moving quarkonium [15], and finite 't Hooft coupling correction [16]. For more studies in different backgrounds, see [17][18][19][20][21][22]. In Refs.…”
mentioning
confidence: 99%